Production of bioethanol from sago hampas via Simultaneous Saccharification and Fermentation (SSF) - HUANG CHAI HUNG; DAYANG SALWANI AWANG ADENI; QUEENTETY JOHNNY; MICKY VINCENT (Smujo International, 2018)
Huang CH, Adeni DSA, Johnny Q, Vincent M. 2018. Production of bioethanol from sago hampas via Simultaneous Saccharification and Fermentation (SSF). Nusantara Bioscience 10: 240-245. Sago hampas is an inexpensive, renewable and abundant agro-industrial residue that can be exploited to produce bioethanol. In this study, ethanol production was performed via simultaneous saccharification and fermentation (SSF) on fresh sago hampas at 2.5%, 5.0% and 7.5% (w/v) feedstock loadings with the aid of amylolytic enzymes, cellulolytic enzymes and Saccharomyces cerevisiae, under anaerobic condition for five days with a constant agitation of 150 rpm and ambient temperature. Results obtained indicated that SSF with 5.0% (w/v) sago hampas loading produced the highest ethanol yield at 17.79 g/L (79.65% Theoretical Ethanol Yield, TEY), while SSF using 2.5% and 7.5% (w/v) sago hampas produced ethanol at only 8.38 g/L (75.00% TEY) and 23.28 g/L (69.48% TEY), respectively. Total biomass reduction was recorded between 66.3% to 71.3% by the end of the SSF period. This study demonstrated that fresh sago hampas is a promising feedstock for bioethanol production as yields are generally high for all the substrate loadings tested. Moreover, bioethanol production using fresh sago hampas may assist in reducing pollution caused by sago waste accumulation.